The effect of the project-based learning model on the soft skill of vocational school students - Hartati, Listyana; Marsono, Marsono; Yoto, Yoto (Technium Social Sciences Journal, 2022)
This study aims to analyze the project-based learning model on the soft skills of SMK students. The Project-Based Learning model requires students to have skills in solving a problem. The approach used in this research is quantitative using ex-post facto research, the type of correlation research. The sample used for the study was 170 students. The results of the study found a significant influence between the Project-Based Learning Model in the Network Infrastructure Administration Subject on students' communication skills, discipline, responsibility, creativity, and collaboration. Through the Project-Based Learning model, teachers are advised to often train students to complete tasks that can improve students' soft skills in other subjects.